Impact of diabetes as a risk factor in patients undergoing subcutaneous implantable cardioverter defibrillator implantation: A single-centre study. (April 2020) - Kaya, Elif; Siebermair, Johannes; Vonderlin, Nadine; Hadjamu, Nino; Azizy, Obayda; Rassaf, Tienush; Wakili, Reza
Introduction: Patients with diabetes mellitus are known to carry an increased risk for surgical site infections and perioperative complications. The subcutaneous implantable cardioverter defibrillator is an established treatment option in patients at risk for sudden cardiac death especially with an increased risk for infection over time. Methods and Results: Forty-eight patients (mean age = 55.0 ± 21.3 years, 31.3% patients with diabetes mellitus, 75% male) who underwent consecutive subcutaneous implantable cardioverter defibrillator surgery between February 2016 and May 2019 were retrospectively analysed. Overall adverse events including relevant bleeding complications, any surgical wound problems and infections requiring reoperation or device malfunction were evaluated as primary combined safety endpoint. Patients with diabetes mellitus tended to be older with a higher body mass index compared to non-diabetes mellitus. Procedure duration and postsurgery hospital days were not different in diabetes mellitus versus non-diabetes mellitus patients. Analysis of the primary combined endpoint showed no significant difference but a trend towards higher event rates in the diabetes mellitus group (diabetes mellitus vs non-diabetes mellitus: 20% vs 12.1%, p  = 0.119). Conclusion: Diabetes mellitus is a frequent and relevant variable in patients undergoing subcutaneous implantable cardioverter defibrillator implantation represented by 31.3% in this consecutive cohort. Our results suggest that diabetes mellitus is not associated with a prolonged hospital stay or increased rate of periprocedural adverse events.